Acute Bilateral Hydro Nephrosis after the Use of Dapagliflozin - Afandi, Bachar; Bernieh, Bassam (Journal of Nephrology Advances, 2016)
Background Dapagliflozin; the new oral hypoglycemic agent; is a sodium-glucose cotransporter-2 (SGLT2) inhibitor that acts by inhibiting glucose reabsorption in the proximal tubule of the nephron. Main reported side effects are osmotic diuresis, dehydration, urinary tract and genital infections. Here, we report a case of acute bilateral hydronephrosis after the introduction of dapagliflozin. Case Presentation A 52 year old nurse lady, with 15 year history of type2 diabetes mellitus (T2 DM) complicated by type4-renal tubular acidosis, hypertension, proteinuria, and hyperlipidemia. Patient had two episodes of UTI’s in 2011 required full urologic work up, were successfully treated with simple courses of oral antibiotics. CT pyelography done in 2011 was normal. Dapagliflozin was added to her therapeutic regimen in March 2015. Results Within 48 hours after starting dapagliflozin, she reported increased urine output. Ten days later; she developed severe bilateral loin and lower back pain, followed by suprapubic pain, dysuria and fever. Urine analysis and cultures confirmed E. coli urosepsis. Renal US revealed echogenic kidneys with 12 mm bilateral hydronephrosis, normal ureters and urinary bladder. Discontinuation of dapagliflozin in April 2015 resulted in resolution of symptoms. Repeat CT of the abdomen in July 2015 revealed no hydro nephrosis. Conclusions This is the first case report of reversible bilateral hydronephrosis after the use of dapagliflozin. The cause of hydronephrosis, could be explained by over-diuresis and/or by the unmasking of underlying subclinical obstruction in both uretero-pelvic junctions (UPJ).
Keywords: Dapagliflozin; Acute hydronephrosis; Overdiuresis; Reversible